Novel triple lumen catheter for ERCP tissue diagnosis - Goetz, Martin; Malek, Nisar P. (Endoscopy International Open, 2018)
Introduction The ideal endoscopic retrograde cholangiopancreatography (ERCP) tissue sampling technique should be simple, inexpensive, and yield sufficient tissue for histology while permitting contrast-guided targeting under fluorescence and multiple passes into the bile duct. Current techniques do not fulfill these requirements comprehensively. We designed a catheter for optimized targeting of large intrabiliary biopsies.Methods A 3.5-mm sterile, single-use prototype catheter was developed, with three independent lumina extending continuously to the distal tip for three distinct functions to be available simultaneously: passage of large volume biopsy forceps (1.8 mm), wire guidance (0.035″), and contrast injection.Results First clinical use in five patients (four transpapillary, one percutaneous access) allowed good intrabiliary manipulation in 4/5 patients. Contrast-guided sampling provided adequate specimens. No adverse events were noted.Discussion Technical aspects and preliminary clinical data for the novel triple lumen biopsy catheter are encouraging. The catheter allowed wire guidance and contrast application to guide sampling of larger pieces of tissue. In perspective, the working channel could host any accessory for targeted intrabiliary diagnosis and therapy, and catheter use is not limited to bile ducts.